2018
DOI: 10.1007/s40858-018-0266-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation and structure of Sclerotinia sclerotiorum populations from soybean in Brazil

Abstract: The clonal, necrotrophic plant pathogen, Sclerotinia sclerotiorum is the causal agent of white mold on soybean, which causes significant losses for Brazilian farmers each year. While assessments of population structure and clonal dynamics can be beneficial for determining effective management strategies, few studies have been performed. In this paper, we present a population genetic analysis with 11 microsatellite loci of 94 isolates of S. sclerotiorum from soybean fields in six Brazilian states

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Sclerotinia sclerotiorum is rich in genetic diversity worldwide [69][70][71][72][73][74][75][76]. Previously, the Chinese S. sclerotiorum population was found to have a greater genetic variance for most of the traits than the US population and they did not share any mycelial compatibility groups or multilocus haplotypes [46].…”
Section: Discussionmentioning
confidence: 99%
“…Sclerotinia sclerotiorum is rich in genetic diversity worldwide [69][70][71][72][73][74][75][76]. Previously, the Chinese S. sclerotiorum population was found to have a greater genetic variance for most of the traits than the US population and they did not share any mycelial compatibility groups or multilocus haplotypes [46].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the major economic crops affected include dry bean, potato, soybean [ Glycine max (L.) Merr. ], sunflower ( Helianthus annuus L.), canola ( Brassica napus L.), lettuce ( Lactuca sativa L.), carrot ( Daucus carota L.), and pea ( Pisum sativum L.) ( Carpenter et al, 1999 ; Mert-Türk et al, 2007 ; Hemmati et al, 2009 ; Attanayake et al, 2013 ; Lehner et al, 2015 ; Abán et al, 2018 ; Panullo et al, 2018 ). In Argentina, WM has been detected in all bean production areas, reaching seed yield and quality losses up to 80–100% on susceptible common bean cultivars under favorable weather conditions ( Singh and Schwartz, 2010 ).…”
Section: White Moldmentioning
confidence: 99%
“…However, other studies have suggested taking into account the structure imposed by the MCGs in addition to a set of molecular markers in population analyses ( Lehner and Mizubuti, 2017 ; Lehner et al, 2019 ; Silva et al, 2021 ). Over the past few years, the population structure of S. sclerotiorum has been extensively documented from different host crops and from different regions in the world ( Atallah et al, 2004 ; Sexton et al, 2006 ; Hemmati et al, 2009 ; Ekins et al, 2011 ; Attanayake et al, 2013 ; Clarkson et al, 2013 , 2017 ; Aldrich-Wolfe et al, 2015 ; Dunn et al, 2017 ; Panullo et al, 2018 ; Faraghati et al, 2022 ). In early studies, S. sclerotiorum populations exhibited a predominantly clonal population structure with low genetic diversity based on MCGs and DNA fingerprinting genotypes ( Kohli et al, 1992 ; Cubeta et al, 1997 ; Hambleton et al, 2002 ).…”
Section: White Moldmentioning
confidence: 99%
See 1 more Smart Citation